2019
DOI: 10.5114/bta.2019.83208
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships of Iranian endemic mint species, Mentha mozaffariani Jamzad and some other mint species revealed by ISSR markers

Abstract: Mint species (Mentha sp.) are important vegetables with medicinal and economic characteristics. In this study, the genetic relationships of 34 accessions of 5 mint species including Mentha spicata, Mentha longifolia, Mentha piperita, Mentha aquatica, and Mentha mozaffarianii Jamzad were evaluated using Inter-Simple Sequence Repeat (ISSR) markers, followed by the analysis of the polymerase chain reaction (PCR) products on a high-resolution acrylamide gel. ISSR primers yielded 74 clear and reproducible bands, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Out of the 421 bands, 416 (98.71%) were polymorphic with an average of 18.90 polymorphic bands per primer (Table 2). Choupani et al (2019) reported that the average number of polymorphic bands and the average percentage of polymorphism were 10.57 and 65.28%, respectively, in 34 genotypes from 5 different species of mint using ISSR markers. This indicates that we have used a more diverse collection of mint genotypes for ISSR analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 421 bands, 416 (98.71%) were polymorphic with an average of 18.90 polymorphic bands per primer (Table 2). Choupani et al (2019) reported that the average number of polymorphic bands and the average percentage of polymorphism were 10.57 and 65.28%, respectively, in 34 genotypes from 5 different species of mint using ISSR markers. This indicates that we have used a more diverse collection of mint genotypes for ISSR analysis.…”
Section: Resultsmentioning
confidence: 99%
“…High intraspecific variability is clear from other molecular studies too (e.g., marker techniques AFLP, RAPD, ISSR and SCoT), which mostly led to very heterogeneous phylogenetic or phenetic results [ 32 , 61 , 98 , 104 ]. Choupani et al [ 111 ] repeat for Spicate and Capitate mints ( M. longifolia, M. spicata, M. aquatica etc.) the remarkable conclusion that intraspecific variability is larger than interspecific variability—a thesis that makes sense in a polyphyletic constellation where cryptic species might hide [ 40 ] (see also many other mutually deviant results as for interspecific relationships and variability in Spicate/Capitate mint species [ 30 , 31 , 60 , 112 , 113 , 114 , 115 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Multi-locus dominant markers such as amplified fragment length polymorphism (AFLP), random amplified polymorphic DNA (RAPD), and intersimple sequence repeat (ISSR) markers have been used with a small number of mint accessions for assessment of genetic diversity and relationships (Khanuja et al, 2000;Gobert et al, 2002;Shasany et al, 2002;Shiran et al, 2004;Vining et al, 2005;Sabboura et al, 2016;Jedrzejczyk and Rewers, 2018;Choupani et al, 2019) and for cultivar identification (Fenwick and Ward, 2001). Species-specific start codon targeted (SCoT) markers were also developed and used to assess genetic diversity in 12 accessions from four mint species (Khanm et al, 2017).…”
Section: Molecular Analysismentioning
confidence: 99%